DISCOHAT: An Acronym to Describe the Spectrum of Symptoms Related to Bilateral Vestibulopathy - Sophie Paredis (Frontiers Media S.A., 2021)
Objective: To assess the prevalence of each symptom listed in the acronym DISCOHAT (worsening of symptoms in Darkness and/or uneven ground, Imbalance, Supermarket effect, Cognitive complaints, Oscillopsia, Head movements worsen symptoms, Autonomic complaints, and Tiredness) in patients with bilateral vestibulopathy (BVP), compared to patients with unilateral vestibulopathy (UVP).Methods: A descriptive case-control study was performed on BVP and UVP patients who were evaluated for their vestibular symptoms by two of the authors (RvdB, MCG) at a tertiary referral center, between 2017 and 2020. During history taking, the presence of each DISCOHAT symptom was checked and included in the electronic health record. Presence of a symptom was categorized into: “present,” “not present,” and “missing.”Results: Sixty-six BVP patients and 144 UVP patients were included in this study. Prevalence of single DISCOHAT symptoms varied from 52 to 92% in BVP patients and 18–75% in UVP patients. Patients with BVP reported “worsening of symptoms in darkness,” “imbalance,” “oscillopsia,” and “worsening of symptoms with fast head movements” significantly more than UVP patients (p ≤ 0.004).Conclusion: The DISCOHAT acronym is able to capture a wide spectrum of symptoms related to vestibulopathy, while it is easy and quickly to use in clinic. Application of this acronym might facilitate a more thorough and uniform assessment of bilateral vestibulopathy, within and between vestibular clinics worldwide.